COMBINATION OF COCOSO AND SAW ALGORITHM TO DETERMINE USED MOTORCYCLES - Dalimunthe, Roni; Yesputra, Rolly; Rohminatin, Rohminatin (JURTEKSI (jurnal Teknologi dan Sistem Informasi), 2024)
Abstract: Used motorbikes are motorized vehicles that are used by many people in various cicles. For someone who is a prospective buyer of a used motorbike, before coming to the place of puchase they have several choices based on several criteria that have been determined according to the used motorbike they want to buy. A problem that often occurs for prospective buyers is the difficulty in determination which used motorbike is superior from several choices based on predetermined criteria. This results in potential buyers feeling confused in making their choice. The difficulty in determining used motorbikes is the reason this research was conducted. In this case, the decision support system will be used as a tool in providing superior used motorbike choices for potential buyers. The method offered in this research is to use a combination of the CoCoSo and SAW algorithms. The criteria for determination a used motorbike consist of 8 criteria namely mileage, price, brand, accessories, tire condition, body condition, engine condition and completeness of documents. In the results of this decision support system research, ranking results using a combination of CoCoSo and SAW methods show that the red Suzuki F1 alternative (A39) is ranked with the highest score.Keywords: combined compromise solution; decision support system; simple additive weighting Abstrak: Sepeda motor bekas merupakan kendaraan bermotor yang digunakan oleh sebagian banyak masyarakat dalam berbagai kalangan. Bagi seseorang calon pembeli sepeda motor bekas, sebelum datang ke tempat pembelian mereka memiliki beberapa ketentuan pilihan yang berdasarkan pada beberapa kriteria yang telah ditentukan sesuai dengan sepeda motor bekas yang ingin dibeli. Permasalahan yang sering kali terjadi bagi calon pembeli ialah kesulitan dalam menentukan sepeda motor bekas mana yang unggul dari beberapa alternatif pilihan berdasarkan kriteria yang telah ditentukan sebelumnya. Hal ini mengakibatkan, calon pembeli merasa kebingungan dalam menentukan pilihannya. Kesulitan dalam penentuan sepeda motor bekas tersebut menjadi alasan penelitian ini dilakukan. Dalam hal ini sistem pendukung keputusan akan digunakan sebagai alat bantu dalam memberikan pilihan sepeda motor bekas yang unggul bagi calon pembeli. Metode yang ditawarkan dalam penelitian ini yaitu dengan menggunakan kombinasi algoritma CoCoSo dan SAW. Kriteria-kriteria dalam penentuan sepeda motor bekas terdiri dari 8 kriteria yaitu jarak tempuh, harga, merek, aksesoris, kondisi ban, kondisi body, kondisi mesin dan kelengkapan surat. Dalam hasil penelitian sistem pendukung keputusan ini, memberikan hasil perangkingan dengan kombinasi metode CoCoSo dan SAW menunjukkan bahwa alternatif Suzuki F1 merah (A39) adalah peringkat dengan nilai tertinggi.Kata kunci : combined compromise solution; simple additive weighting; sistem pendukung keputusan